Public utility jeepney drivers in Bacolod City, Negros Occidental socio-economic conditions and income differentials analysis. - Banagodos, Lorena Joy Paderna (1997.)
Benchmark information was sought regarding the socio-economic conditions of jeepney drivers and their households from a sample of 111 respondents in Bacolod City, Negros Occidental. This profile focused on their socio-demographic and housing characteristics as well as their household expenditure patterns. Several aspects of the driving occupation was also discussed. Income differentials analysis was also used to determine the factors that significantly accounted for the variability in driving income., Drivers were mainly composed of married and middle-aged men, majority of whom were high school graduates. Average household size was from 4-5 members with father-driver as the only earning family member. Income from jeepney driving accounted for over half of monthly total household income averaging at P4,039.73. Drivers houses were made of GI roofs, and wooden outer walls. Most of the sample personally owned their housing units but were squatting on other people's lands. Their houses were equipped with electricity for lighting, LPG for cooking, manual pumps for drinking water and exclusive water-sealed for toilets. Food accounted for over 60 of the driving households expenditures followed by education, utilities, and medical care. Out of their expenditures, the driving household were still able to save less than 10 of their total incomes. Operator driver households had higher expenditure levels than boundary driver households. On the average, the drivers total expenditures were higher than the 1996 inflated food and poverty thresholds. Their income-expenditure patterns reveal a discrepancy of P1414.21 between their total household income and total household expenditures which means that the drivers households have higher chances of increasing their savings levels. Driving experience averaged at 16 years. Consisting mainly of boundary drivers, majority of the sample had 16-seater and diesel-fueled jeepneys. Striking rounds were mostly done during peak hours (7-9AM, 11-1PM, and 4-7PM) while parking rounds were done during lean hours (9-11AM and 1-3PM). Drivers were largely free to choose how long and how often to work in a day or week. They drove for six days weekly and averaged nine hours per day. Passing by 10-16 schools, jeepneys which traversed four routes (Bata-Libertad, Shopping-Libertad, Banago-Libertad, and Mandalagan-Libertad jeepneys) had relatively higher mean incomes than the rest of the sample. Boundary drivers had higher reported boundary fees and lower daily incomes than operator drivers. The sample's average driving income breaks even with the daily poverty threshold for a family of six members. Only 36 had SSS memberships. Drivers largely shouldered the vulcanizing, fuel, association membership fees and traffic violation penalties of utility vehicles while operators largely assumed its expenses for vehicle-related violations, spare parts, repair, and maintenance needs. The subject-respondents considered the small volume of passengers on some routes, the high cost of penalties from traffic violations, the unscrupulous apprehensions of traffic enforcers, the proposed traffic rerouting scheme and the labor-intensiveness of the occupation as some of its most pressing problems. The postulated regression model was determined to be highly significant with an F-computed value of 7.964. The t-test and p-values, likewise, indicated four independent variables (number of schools passed, the capacity of the vehicle, the number of accounted for about 39 of the variability in driving income.
Thesis (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Drivers -- Public Utility Jeepney -- Income